BODILY PRACTICES AND RELIGIOSITY: DISCOURSES OF RELIGIOUS LEADERS (Fiep Bulletin - online, 2014)
The body and religiosity subject situated in the scope of the bodily practices is a theoretical production seldom discussed in academic circles, especially in Physical Education. The objective is to verify the relation between bodily practices and religiosity, as well as the possible influence of the religious institutions in the practices of physical activities / bodily practices. The study used the sacred and profane categories based in Elíade (1992) and control, power and authority by the institutions according to Foucault (1987). The speech analysis was used to interpret the interviews performed with five religious leaders from the following churches: Baptist, Assembléia de Deus (God's Assembly), Maranata, Universal do Reino de Deus (God's Kingdom Universal) and Adventista do Sétimo Dia (Seventh Day Adventist). The interviewed leaders belong to the city of Vila Velha - ES. The verbal message was used for this study, with inferences of the data achieved in the answers from the religious leaders. It was concluded that there are restrictions for the practice of physical activities. Regarding the indication of activities, the leadership is not against it as long as they are subjected to the institutions. It is noticed that, although the practice of the activities obey to several behavior standards, the body does not escapes from the vigilance and control of the institutions. It was noticed, in the speech of the interviewed, a clear comprehension of the body in two different sides: body and soul facing the used bibliographic references.
Keywords: Bodily practices; Sacred; Profane